Sustainable Laccase Production by Anoxybacteroides rupiense UE27 Using Desmostachya bipinnata Biomass: Optimisation and Application in Textile Effluent Treatment - Haniah Saeed; Bushra Rehman; Uroosa Ejaz; Maria Muhammad Ashraf; Amal Siraj; Areesha Mustafa; Muhammad Sohail (Environmental Microbiology, 2026)
Laccase has been widely reported for the detoxification of industrial effluents, yet large‐scale applications require cost‐effective production. This study utilised an innovative approach by employing biomass from the halophyte Desmostachya bipinnata, which has not been previously reported for microbial enzyme production. A newly discovered bacterial species, Anoxybacteroides rupiense, was used for laccase production. Initially, the factors impacting laccase production by the thermophilic strain of A. rupiense UE27 (Genome Project JBHLFH010000000.1) were screened for their significant effects using the Plackett–Burman design. Consequently, Response Surface methodology was adopted to optimise the significant factors, resulting in a maximum laccase yield of 51.69 U L −1 at pH 6.39 and in presence of 0.59 mM CuSO 4 , representing a 4.29‐fold increase compared to the unoptimised conditions. AFM revealed comminution in the plant biomass and FTIR analysis confirmed laccase‐mediated lignin degradation in D. bipinnata biomass, evidenced by shifts in aromatic CC (1597–1650 cm −1 ), CH methyl (2850–2918 cm −1 ) and phenolic OH (3300–3400 cm −1 ) regions. Moreover, growth of A. rupiense UE27 in the presence of textile effluent resulted in 70.6% decolourisation with the subsequent laccase production. Hence, this study presents a sustainable and innovative approach for developing wild biomass‐based processes for the cost‐effective production of laccase by thermophilic bacteria.